(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article studies the theoretical and practical aspects of ensuring the stability of the national economy and the national currency of Uzbekistan. The main factors affecting the stability of the national economy and currency are studied, the level of inflation, monetary policy, the state of the foreign exchange market, foreign direct investment and the foreign trade balance are analyzed. Special attention is also paid to the monetary policy of the Central Bank and its impact on economic stability. Within the framework of the study, existing problems were identified and appropriate recommendations and conclusions were formulated on their solutions.